Linguistic analysis of Philippine crime news broadcasts - William Mel Coranes Paglinawan (Universitas Ahmad Dahlan, 2021)
News stories on negative phenomena such as crime news can stir diverse angles of reality which result in diverse forms of behaviors. This study examined the linguistic devices and discourse strategies employed by the Filipino Journalists in constructing crime news broadcasts. The Linguistic Analysis (LA) framework using the lens of Ilya Romanovich Galperin and van Dijk's Socio-Cognitive Model were used; in which 25 mainstream crime news broadcasted in the Philippine TV from January to May 2015 were collected and transcribed. The findings revealed that phonetic devices such as alliteration, cacophony, assonance, rhyme and onomatopoeia were present in the corpus; lexical devices like epithet, metonymy, epigram, pleonasm, personification, and zeugma; and, syntactical devices such as enumeration, gap-sentence-link, asyndeton, rhetorical questions were mostly demonstrated in the sentences of the research corpora. Moreover, Filipino Journalists had utilized strategies such as, use of figures and statistics, metaphorization; authoritarianism; blame transfer; dysphemism; positive-self and negative-other; and source avoidance strategy. These devices and strategies made most of the statements contextual and implied. In addition, it was also revealed in the analyses that Philippine dialectical terms and neologisms were evident strategies used by the Filipino Journalist in assisting audiences to better appreciate, comprehend and discover the truth in news broadcasting.